AT et la sémantique des prépositions - Dominique Boulonnais (Anglophonia)
This paper examines the semantics of AT in English, with a view to accounting for the way prepositional constructions are learned in a usage-based approach to language.Prepositions in their primary uses are shown to be both case and theta-role assigners, whose distribution in language use is semantically determined by their core value. The latter is established through the analogical processes which control the development of variables in the corresponding prepositional constructions.It is argued that AT has two main uses : an autonomous use in which the PP denotes a spatial or temporal adimensional landmark (there/then) and a dependent one in which the PP becomes part of a construction headed by a governing element, verb, adjective or noun (at + pronoun). AT PPs can instantiate three argument positions, Trigger, Target and Domain, depending on the governing element.The paper also discusses two values which are commonly associated with AT in governed PPs, namely aggressiveness and incompleteness, to show that neither can be considered as part of the core meaning of the preposition.